2021
DOI: 10.3233/jnd-210670
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to DMD Care Considerations in the Netherlands

Abstract: Background and objective: To optimize care for patients with DMD, it is essential to know to what extent current care complies with the recommended monitoring frequencies suggested by the DMD care considerations. The objective of this study was to investigate the current care for patients with DMD in the Netherlands and to what extent the care complies with the international care considerations. Methods: A cross-sectional questionnaire was carried out among the Dutch DMD patients and caregivers about the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Other treatment strategies include surgery for the correction of scoliosis, assisted cough and ventilation support, use of ankle-foot orthoses, cardiac management, and psychosocial care [7,8]. To optimize the treatment results, it is important that patients adhere to care recommendations; however, some studies showed a suboptimal compliance [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Other treatment strategies include surgery for the correction of scoliosis, assisted cough and ventilation support, use of ankle-foot orthoses, cardiac management, and psychosocial care [7,8]. To optimize the treatment results, it is important that patients adhere to care recommendations; however, some studies showed a suboptimal compliance [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary care has been associated with better adherence to clinical follow-up, resource utilization, and quality of life [4]. However, there is limited knowledge regarding the compliance with these recommendations, and when studied, such as in DMD, there are many barriers to successful practice [5]. To our knowledge, there is inadequate use of multidisciplinary teams and sparse research on the topic.…”
mentioning
confidence: 99%